Olympic and World Championship track and field athletes` experiences during the specialising and investment stages of development: a qualitative study with Australian male and female representatives - Huxley, D. J.; O`Connor, D.; Bennie, A. (Journal of Quantitative Analysis in Sports, 2018)
Athlete talent development literature has revealed high attrition rates of elite junior athletes during their mid-to-late adolescence (age 15-19 years) across a range of sports, including track and field (T&F). However, much of the research has focused on early athletic participation during the sampling stage rather than the transition from junior elite to senior elite representation. Based on the Developmental Model of Sport Participation (DMSP), this study investigated factors during the specialising and investment stages that underpinned the development of 14 elite Australian junior T&F athletes who transitioned into elite senior careers. Semi-structured interviews were employed to elicit a deep understanding of the 14 athletes` developmental experiences. Inductive thematic analysis revealed four major dimensions of talent development during the specialising and investment stages - training, competition, social support and personal factors. Early training and competition experiences for elite Australian T&F athletes were commensurate with the specialising stage of the DMSP, where athletes balanced involvement in various sports with T&F. The findings from the present study confirm that most athletes were late specialisers, and did not focus on their main senior event and were not ready to fully investment in specialised intense training until towards the end of the investment stage. Athletes revealed experiences at junior international competitions, support from parents and peers and knowledge and guidance of coaches to their appropriate developmental stage were instrumental in their development. Overall our findings provide further support to the DMSP model recommendation that young athletes are not physically or psychosocially ready to enter the investment stage at least age 16 years.